The association between local hospital segregation and hospital quality for medicare enrollees - Ellesse-Roselee L. Akré; Deanna Chyn; Heather A. Carlos; Amber E. Barnato; Jonathan Skinner (PLoS ONE, 2025)
There is considerable racial segregation in U.S. hospitals that residence alone cannot explain. Little is known about how this patient sorting affects racial inequalities. We use 2019 Medicare claims data linked to CMS Overall Hospital Quality Star Ratings to measure how the sorting of Black patients to different hospitals within the same healthcare markets affects racial gaps in hospital quality. Defining a hospital’s market based on driving time, we use the local hospital segregation (LHS) index to measure racial sorting within a market; this measures the hospital’s disproportionate share of Black patients relative to the hospital’s market. In the sample of 2,163 hospitals, we find a 10 percent point increase in the LHS was associated with a 79% increase in the risk of being admitted to a lower-quality hospital. Thus, hospitals receiving a disproportionate share of Black patients due to market segregation are of systematically lower quality. A better understanding of hospital choice drivers could help reduce racial inequalities in health outcomes.